2011
DOI: 10.1038/gt.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Ocular gene delivery using lentiviral vectors

Abstract: Substantial advances in our understanding of lentivirus lifecycles and their various constituent proteins have permitted the bioengineering of lentiviral vectors now considered safe enough for clinical trials for both lethal and non-lethal diseases. They possess distinct properties that make them particularly suitable for gene delivery in ophthalmic diseases, including high expression, consistent targeting of various post-mitotic ocular cells in vivo and a paucity of associated intraocular inflammation, all co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 81 publications
0
57
1
2
Order By: Relevance
“…For example, introduction of Ad-5 to the superior colliculus or to the transected optic nerve stump results in retrograde transport of viral particles and subsequent gene expression in some RGCs. 28 Subretinal injection of lentiviral vectors results in transgene expression primarily by RPE cells, although other cells, including some photoreceptors, bipolar cells and Müller glia, may occasionally be transduced (see review by Balaggan et al 29 ). Some studies have observed limited transduction of the inner retina when HIV-1 vectors are delivered intravitreally, 8 whereas others have reported some transduction of RGCs following intravitreal injection of HIV-2 vectors.…”
Section: Tools For Gene Delivery To Injured Rgcsmentioning
confidence: 99%
“…For example, introduction of Ad-5 to the superior colliculus or to the transected optic nerve stump results in retrograde transport of viral particles and subsequent gene expression in some RGCs. 28 Subretinal injection of lentiviral vectors results in transgene expression primarily by RPE cells, although other cells, including some photoreceptors, bipolar cells and Müller glia, may occasionally be transduced (see review by Balaggan et al 29 ). Some studies have observed limited transduction of the inner retina when HIV-1 vectors are delivered intravitreally, 8 whereas others have reported some transduction of RGCs following intravitreal injection of HIV-2 vectors.…”
Section: Tools For Gene Delivery To Injured Rgcsmentioning
confidence: 99%
“…Les lentivirus (Lv) sont des rétrovirus à ARN ayant une capacité de chargement d'ADN d'environ 8 à 10 kb ; ils s'intègrent dans le génome de l'hôte [14]. Bien qu'aucune transformation maligne n'ait été rapportée dans les yeux de souris en utilisant des titres élevés de lentivirus [14], la question de la mutagenèse insertionnelle continue d'être étudiée par la génération de lentivirus dits « non intégrants » et l'utilisation de lentivirus issus de primates non humains [14].…”
Section: Les Lentivirusunclassified
“…Bien qu'aucune transformation maligne n'ait été rapportée dans les yeux de souris en utilisant des titres élevés de lentivirus [14], la question de la mutagenèse insertionnelle continue d'être étudiée par la génération de lentivirus dits « non intégrants » et l'utilisation de lentivirus issus de primates non humains [14]. De nombreuses études montrent que, lorsqu'ils sont injectés par voie sous-rétinienne, les lentivirus transduisent efficacement l'épithélium rétinien pigmentaire chez les rongeurs [15,16], mais la transduction des photorécepteurs reste variable [17,18].…”
Section: Les Lentivirusunclassified
“…Many studies over the past years have provided evidence of the higher efficiency of viral versus nonviral vehicles (Andrieu-Soler et al, 2006) for retinal gene delivery; however, recent reports on nanoparticle-mediated retinal gene therapy showed an improvement compared with previous studies with nonviral agents (Cai et al, 2008). The vectors most studied and used for retinal gene transfer are those derived from adenoviruses (Kumar-Singh, 2008), lentiviruses (Balaggan and Ali, 2012), and adeno-associated viruses (Vandenberghe and Auricchio, 2012) which are capable of infecting and transducing nondividing cells such as PRs and RPE.…”
Section: Efficient Viral Vectors Are Key Elements For Successful Retimentioning
confidence: 99%
“…LVs are integrating RNA retroviruses with a cargo capacity of about 8-10 kb (Balaggan and Ali, 2012). LVs are deleted of all viral genes and, thus, do not activate the immune system (Bennett, The PR OS is formed by an elaborate system of stacked membranous discs that contain the photosensitive opsin proteins.…”
Section: Efficient Viral Vectors Are Key Elements For Successful Retimentioning
confidence: 99%